Penerapan Kode Etik Foto Jurnalistik Pada Berita Hukum Dan Kriminal Di Harian Banyuasin - Mustri Liza; Amin Sihabuddin; Sumaina Duku (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The issue of photojournalism that deviates from the Photojournalism Code of Ethics is what prompted this investigation. The purpose of this research is to understand how the Code of Ethics is applied to legal and criminal news photos in Banyuasin Daily. This research uses a qualitative approach. While the type of data uses primary and secondary data to document observations, interviews, and other data collection methods. In addition, data reduction, data presentation, and data verification were used in the data analysis process, which ended with checking the accuracy of the data. The author used qualitative techniques in his research. Investigating the state of nature by using the researcher as the main tool is known as qualitative research. In addition, this research includes people, events, and documents. Human data sources are the words and actions of individuals who are able to contribute information through documentation, observation, and interviews. Snowball sampling is the approach used, where the author can add more data to fill in the gaps. Based on the research findings, it can be said that journalists' opinions regarding the application of the Journalism Code of Ethics are generally not in line with the legal regulations governing the work of journalists based on the Code of Ethics. Similarly, the Journalism Code of Ethics regulates how journalists and media should behave when publishing photos in news reports. Of course, Banyuasin Daily Media, like any other media, will try to adhere to the Photojournalism Code of Ethics in every story; however, this is not always as simple as it seems because editorial teams and field journalists do not always communicate well, and the speed of reporting sometimes overlooks photos. In addition, carelessness or failure can obscure the images included.